2019
DOI: 10.1177/1078155219867131
|View full text |Cite
|
Sign up to set email alerts
|

Durable response after discontinuation of nivolumab therapy in the absence of disease progression or toxicity with two advanced NSCLC patients

Abstract: Background Nivolumab is an immune checkpoint inhibitor that selectively blocks the programmed cell death-1 (PD-1). Nowadays, immune checkpoint inhibitors such as nivolumab are used in the treatment of many different types of cancer. In prospective clinical trials, the duration of therapy with nivolumab has been defined as up to the time of progressive disease or treatment limiting toxicity. Case reports In this article, we present two advanced non-small cell lung cancer (NSCLC) patients that were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Although it is reportedly better to maintain ICIs, all patients who achieved CR were long‐term survivors and had no signs of disease relapse 15 . However, there is no clear evidence on how long treatment should continue 16,17 . Other studies have reported that the drug was effective once it was discontinued and readministered when it recurred 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is reportedly better to maintain ICIs, all patients who achieved CR were long‐term survivors and had no signs of disease relapse 15 . However, there is no clear evidence on how long treatment should continue 16,17 . Other studies have reported that the drug was effective once it was discontinued and readministered when it recurred 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…15 However, there is no clear evidence on how long treatment should continue. 16,17 Other studies have reported that the drug was effective once it was discontinued and readministered when it recurred. 18,19 If the tumor completely disappears as in the present case, then it may be possible to administer pembrolizumab for a certain period, discontinue it, and if cancer recurs, re-challenge it.…”
Section: Discussionmentioning
confidence: 99%
“…The question of whether durable remission could be maintained after stopping ICI similar to our case necessitates further studies; however, two recent case series have yielded positive results. One of them even concluded that durable response could be achieved after discontinuation of ICI in the absence of toxicity [17-18]. This point of view shall be appreciated by patients who develop intolerable adverse effects or lack enough financial support for ceaseless ICI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although a similar analysis has not been performed (to our knowledge) for patent-protected parenteral drugs, there are some important opportunities, best exemplified by the immune checkpoint inhibitors. [49][50][51][52][53][54] Furthermore, because many patients treated with immune checkpoint inhibitors have prolonged progression-free survival (PFS) despite treatment discontinuation (e.g., due to adverse events), [55][56][57][58][59][60] the optimal duration of treatment is unknown. [61][62][63] Strategy to Identify Candidate Drugs for Financially Guided Dosing…”
Section: Overviewmentioning
confidence: 99%